LW-8 TREATMENT STRATEGY FOR OLIGODENDROGLIOMAS WITH NEOADJUVANT STRATEGY AND STAGED RESECTION UTILIZING THEIR CHEMOTHERAPEUTIC RESPONSIVENESS. (3rd December 2022) - Sasaki, Hikaru; Kanazawa, Tokunori; Kitamura, Yohei; Nakaya, Masato; Fujiwara, Hirokazu; Kimura, Tokuhiro; Nakae, Shunsuke; Ohba, Shigeo; Nishiyama, Yuya; Toda, Masahiro; Yoshida, Kazunari; Hirose, Yuichi
Abstract: Background: In glioma surgery, both of functional preservation and maximal safe resection are critical, however, neoadjuvant strategy has never been used because of difficulty of tissue sampling without craniotomy. Method: In Keio University Hospital, oligodendrogliomas, i.e., diffuse gliomas with IDH mutation and 1p/19q codeletion, with incomplete initial resection have been treated by upfront chemotherapy and subsequent resection after tumor volume decrease (second look resection, SLR) since 2006 (J Neurooncol 124:127-35, 2015). At first, initial radiotherapy was prescribed immediately after chemotherapy or SLR only for the cases with aggressive clinical course or subarachnoid infiltration, however, cases with residual FLAIR abnormality after upfront chemotherapy or SLR were also subjected to initial radiotherapy since 2018. Cases 1) with IDH mutation and 1p/19q codeletion, and 2) without history of either chemotherapy or radiotherapy, and 3) treated with upfront chemotherapy and subsequent resection strategy, were included. Results: Thirty nine cases of oligodendroglioma have been treated with the above strategy since 2006. Tumor volume decrease following upfront chemotherapy was 30-35% (median), and 19 tumors underwent SLR. Among the total 39 cases, PFS and OS after initiation of upfront chemotherapy were 81 months and not reached, respectively, and were 64 months and not reached, respectively, among the 32 cases with deferred radiotherapy. Importantly, the majority of tumor recurrence occurred at the residual FLAIR abnormality following upfront chemotherapy. Conclusions: Treatment of oligodendrogliomas utilizing neoadjuvant strategy enables 1) decrease of resection volume as compared with initial maximal safe resection, 2) more precise resection, 3) confirmation of the necessity of initial radiotherapy based on the observed efficacy of chemotherapy. Moreover, the study also suggested that 4) invasion front of oligodendroglioma likely withdraw by alkylating agents, and 5) cases with residual FLAIR abnormality following chemotherapy may be appropriate subjects for initial radiotherapy.